Sodium Chloride in Food - Sylwia Chudy; Agnieszka Makowska; Ryszard Kowalski (Foods)
Sodium chloride is a chemical compound that has been encountered by people for thousands of years, and plays a significant role in their lives. The aim of this article is to provide a comprehensive review of table salt from the perspective of health, food technology, and cultural heritage. The article discusses salt extraction and production, its composition and consumption, and its effects on the human body. The authors draw attention to new trends, such as the use of micronized salt, microencapsulated salt, and salt with colors and shapes that differ from those of typical table salt. Scientific studies on the presence of undesirable substances and the use of salt additives were reviewed. The role of salt in dairy, meat, and bakery technology was illustrated. Gaps in research on salt were highlighted. In the last part, all types of salt with geographical indications are shown. The paper suggests that producers with a long tradition in the salt sector should apply for the European geographical indications to enhance their national and cultural heritage and promote their region. The review highlights the need for further research on all aspects discussed.